2019
DOI: 10.1002/acn3.771
|View full text |Cite
|
Sign up to set email alerts
|

Plasma proteome in multiple sclerosis disease progression

Abstract: Background: The pathophysiology of multiple sclerosis disease progression remains undetermined. The aim of this study was to identify differences in plasma proteome during different stages of MS disease progression. Methods:We used a multiplex aptamer proteomics platform (Somalogic) for sensitive detection of 1129 proteins in plasma. MS patients were selected and categorized based on baseline and a 4-year follow-up EDSS (delta EDSS) scores; relapseonset (RO) slow progression (n = 31), RO with rapid progression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 37 publications
2
27
0
Order By: Relevance
“…In fact, the changes in the biochemical composition of blood plasma are relatively minor compared to changes in CSF, and they do not necessary reflect all possible alteration occurring in the CNS during the progression of the MS disease. A number of molecular biomarkers for MS disease identified in both plasma and CSF were proposed [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the changes in the biochemical composition of blood plasma are relatively minor compared to changes in CSF, and they do not necessary reflect all possible alteration occurring in the CNS during the progression of the MS disease. A number of molecular biomarkers for MS disease identified in both plasma and CSF were proposed [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many researches have shown that RGMa plays an important role in MS. Demicheva et al reported that the expression of RGMa was significantly increased in acute and chronic damaged plaques and normal white matter of CNS in MS patients [ 22 ]. The level of RGMa in the baseline blood was negatively correlated with the changes of Expanded Disability Status Scale (EDSS) in MS patients, indicating that the level of RGMa was closely related to neurological function [ 2 , 6 , 37 ]. The possible pathogeneses of RGMa in MS include the following: Abnormal signal transduction of immune cells: since IL-17-expressing CD4 + T cells (Th17 cells) strongly expressed RGMa, so the combination of RGMa and Neogenin on immune cells can enhance the immune cell adhesion, promote their invasion to the brain, and enhance T cell response [ 5 , 37 ].…”
Section: Rgma As a Therapeutic Target In Cns Disordersmentioning
confidence: 99%
“…In addition, as a coreceptor of bone morphogenetic proteins (BMPs), RGMa can bind to BMP-2, BMP-4, and other BMP family molecules and participate in iron metabolism, bone development, and axon regeneration through the BMP-BMPR signaling pathway [ 2 , 5 ]. Currently, a number of studies have shown that RGMa is highly expressed in the injured lesions in patients with multiple sclerosis, neuromyelitis optica spectrum diseases, cerebral infarction, spinal cord injury, and Parkinson's disease [ 6 11 ]. It has also been reported that it can promote the functional recovery of the nervous system by inhibiting RGMa [ 6 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AD may be associated with aberrant gene expression and RNA metabolism [2,3], accompanied by cell death and clearance of cells from the brain [4]. There have been many proteomic studies to date focused on nding biomarkers for neurological diseases [5]. A peptide extraction using SDS-PAGE followed by electro elution onto MALDI chips identi ed Fibrinogen β chain FGA/B, AHSG and SERPING1 and biomarkers of AD [6].…”
Section: Introductionmentioning
confidence: 99%